ANALISIS FAKTORâFAKTOR YANG MEMPENGARUHI PERILAKU WAJIB PAJAK TERHADAP PENGGUNAAN E-FILING (Studi pada Wajib Pajak Orang Pribadi Di KPP Semarang Tengah Satu) - Ade Lina Rosita Putri, 13.05.51.0170; Setyowati, Widhy (Students Journal of Accounting and Banking, 2017)
This study aimed to analyze Factors Influence the behavior of taxpayers against the use of e-filing (the study of individual taxpayers in KPP Semarang Tengah Satu). Factors that influence the behavior of the taxpayer among his perceptions of usefulness, perception of ease, security and confidentiality, and user satisfaction. The sampling method in this study uses convenience sampling in data display.Methods of data collection were conducted by questionnaire. Data testing techniques used in this study with multiple regression analysis. The results showed that the perception of usability had no significant effect on the use of efiling. Furthermore, ease perception variable has a significant positive effect on the use of e-filing. While security and secrecy have no significant negative effect on the use of e-filing. The user satisfaction variable shows a significant positive result on the use of e-filing.Keywords: Use of e-Filing, Perception of Usability, Perception of Convenience, Security And Confidentiality, and User Satisfaction